The Relation Between Volume of ACL Reconstruction and Future Knee Surgery. Issue 7 (21st July 2017) - Schairer, William W.; Marx, Robert G.; Dempsey, Brendan; Ge, Yile; Lyman, Stephen
Objectives: A large body of volume-outcomes literature has now demonstrated a strong positive relationship between increasing annual surgical volume and improved patient outcomes across a wide variety of surgical procedures, including orthopedics. Unfortunately, most previous research has been limited by methods that arbitrarily assign cutoffs of "low" or "high" volume that may not be clinically meaningful. Thus, it is unknown how many cases should be performed each year to maintain competence in the procedure. The purpose of this study was to determine meaningful annual volume thresholds for ACL reconstruction. Methods: We identified ACL reconstructions performed in New York (NY) State hospitals between 2003 and 2014 using the NY-SPARCS hospital in-patient and ambulatory surgery database. These cases were followed until subsequent ipsilateral knee surgery (revision ACL, meniscus/cartilage surgery, or total knee replacement) or until the end of the study period, December 31, 2014. Surgeon volume was calculated as the number of ACL reconstructions performed by that surgeon in the 365 days prior to the case of interest. Stratum specific likelihood ratio (SSLR) analysis is a method to identify clinically meaningful cutpoints by correlating volume with outcomes through evaluating a receiver operating characteristic (ROC) curve. A Cox proportional hazards model was used to measure the effect of surgeon annual ACL reconstruction volume on risk of subsequent ipsilateral knee surgery adjusting for patient characteristics: age, sex, race, and insurance type. Results: Between 2003 and 2014, 77, 899 ACL reconstructions were performed in NY State by 1, 316 surgeons. Mean patient age was 30.8+/- 12.5 years, and patients were 61% male, 65% white race, and 74% covered by private insurance. SSLR analysis revealed 2 meaningful cutpoints in risk of subsequent ipsilateral knee surgery: 17 & 35 cases per year. The Cox proportional hazards model demonstrated a 29% decreased risk of ipsilateral knee surgery for those ACL reconstructions by surgeons performing >35 cases per year compared to those performing <17 (Hazard Ratio [HR] 1.29, 95% confidence interval [CI] 1.23-1.35, p<0.001). Further, surgeons in the mid-range group performing 18-35 ACL reconstructions per year demonstrated a 6% decreased risk of subsequent ipsilateral knee surgery (HR 1.06, 95% CI 1.01-1.11, p=0.014). Conclusion: This study identified three ranges for ACL reconstruction volume that result in different clinical outcomes. The highest cutpoint was 35 ACL reconstructions per year, which resulted in the lowest percentage of future knee surgery. These findings suggest orthopedic surgeons should perform a minimum of 35 ACL reconstructions per year to maintain clinical competence with the procedure.